The Role of Fisheries Non-Government Organizations to The Activities of Fisheries In Tapanuli Tengah Regency North Sumatera Province - Husnul Yaqin Harahap; Hendrik '; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research held on the 11thjune-24june 2016 in Tapanuli Tengah Regency the Province of North Numatera. The purpose of this research to find activities of Non-Government Organizations Fisheries, know the funding source of Non-Governmen Organizations, and know the role of Non-Government Organizations to the activities of fisheries, and know relations and cooperation non-governmental organizations fisheries With local Governments or private companies in Tapanuli Tengah. The methodology that was used is a method of case studies.Based on the research result there are fourNon-Government Organizations moving at the focus of the field of fisheries are NGO Manajemen Lingkungan Pesisir dan Kelautan (MLPK), NGO Wahana Lestari, NGO Samudera Hindia Utama, and NGO DPC HNSI Tapanuli Tengah. The Non-Government Organizations conduct activities training fisheries Devoted to fishermen, Wives fishermen, the community, and the educated group. The funding source of Non-Governmental Organization derived from swdaya, donors, and bonds of cooperation or contract. The role of Non-Government Organizations Fisheries to the activities of fisheries are as the initiator, facilitator, supervisor, Mentor and instructors.Key Word : Non-Government Organizations, Activities, Fisheries